The greater journey : Americans in Paris - McCullough, David G. (Detroit : Cengage Learning, 2011)
Relates the story of the American artists, writers, and doctors who traveled to Paris in the nineteenth century, fell in love with the city and its people, and changed America through what they learned there.
Subtitle from container.
"Unabridged selections"--Container.
Compact discs.
Read by Edward Hermann and the author.
English Language & Literature.
Keywords: Americans -- France -- Paris -- Biography; Americans -- France -- Paris -- History -- 19th century; Intellectuals -- France -- Paris -- History -- 19th century; Artists -- France -- Paris -- History -- 19th century; Authors, American -- France -- Paris -- History -- 19th century; Physicians -- France -- Paris -- History -- 19th century; Paris (France) -- Biography; Paris (France) -- Intellectual life -- 19th century; Paris (France) -- Relations -- United States; United States -- Relations -- France -- Paris; Audiobooks